Shear bond strength of two ceramic repair system to lithium disilicate: An in-vitro comparison - Sinaga, Valentine Rosadi; Bonifacius, Setyawan; Sumarsongko, Taufik (Universitas Padjadjaran, 2021)
Introduction: The improvement of ceramic has increased due to highly demand for aesthetic restoration. Ceramic at its nature is a brittle material that highly susceptible to be cracked, that leads to chipping and fracture of the restoration. Composite resin frequently used as a replacement for ceramic repair as a simple and fast solution. The success relies on the bond strength between ceramic and composite. The purpose of this study was to evaluate the shear bond strength of two ceramic repair system to low-glass ceramic lithium disilicate. Methods: This study was experimental laboratory, ten specimens of lithium disilicate ceramic was fabricated. Specimen was divided into two groups, first group include: grinding and treated with ceramic primer and second group: acid etching with hydrofluoric acid and treated with silane. Each specimen was subjected to a shear load at the parallel speed of 0,5mm/minutes until fracture using universal testing machine. Results: The shear bond strength achieved in group two (acid etching and silane) was higher than the group one (grinding and ceramic primer). The t-test one tailed analysis yielded p value 0,0057. The different was significant (p value < 0,05). Conclusion: In this study it is concluded that when treated with acid etching hydrofluoric acid and silane, lithium disilicate yielded higher bond strength with resin composite than when treated with grinding and ceramic primer.